FILM TEXTS “SNOW” AND “TEARS FOR SALE”: “WOMEN’S” CHRONOTOPES AND NARRATING THE LOSS (Philological Studies, 2019)
Primarily referring to Bakhtinʼs concept of chronotope, in this paper we scrutinize the idea of “women’s” chronotope as womenʼs space-time in film texts “Snow” (“Snijeg”) directed by Aida Begić and “Tears for Sale” (“Čarlston za Ognjenku”) directed by Uroš Stojanović, both narrating the lives of women on the margins of war. We juxtapose the traditional concept of “women’s” time (Julia Kristeva) as cyclic and non-linear, and “menʼs” linear time, positioning the female subject outside the progression of “menʼs” time, the time of history. Further, we identify two women’s chronotopes (fictional topoi – villages Pokrp in Serbia and Slavno in Bosnia) as places of mourning, following Freudʼs concept of the mourning process which terminates in overcoming the trauma caused by the loss of beloved object (men killed in wartime). In those film texts we distinguish narrating the loss through ritual and symbolic acts of invoking the missing male subject, and on the other hand, we identify the strategy of overcoming the trauma through gender roles inversion and adoption of masculinity (the woman assumes the active principle and she becomes the bearer of the gaze [Laura Mulvey]). We further differentiate Bakhtinʼs chronotope meeting motif in the aforementioned film texts within the framework of the regeneration chronotope (suggesting a happy ending in “Snow” in a certain way) and the degradation chronotope, in “Tears for Sale” (Bemon and Borghart).
Keywords: chronotope, women’s time, history time, mourning, trauma, masculinity